“Whatever Did Ever Happen to the Likely Lads”? Social Change, Mobility, Class, and Identity in the UK 1969–2019. - Warren, Jon (Frontiers in Sociology, 2020)
This paper reflects upon issues of class and identity in the UK over the last 50 years. 1969 is a useful starting point, economically and technologically it can be regarded as the high tide of the vision of a Britain remade in what the then Prime Minister Harold Wilson had termed “the white heat of technology.” That technology had produced Concord the world's first supersonic airliner which made its debut that year. This successful Anglo French collaboration also showed how Britain was rapidly moving into a different relationship with Europe a process that culminated in the UK's entry into the EEC or the “common market” as it was more usually referred to on January 1st 1973. Sociologically, it marked the publication of Goldthorpe et al. Affluent worker studies, which examined the idea that increasing affluence was breaking down established class structures, roles and attitudes. This debate about whether the changing nature of work brought with it a fundamental change in class structure and identity has been going on ever since. It has subtly changed and this is to be expected, 50 years is a long time. However, it is generally accepted that the change to economic and social policy that had followed the second world, social mobility was increasingly evident by the late sixties and continued into the seventies. Over the years issues of not only social class but de-industrialization, social mobility, regional decline, globalization, and its impact on policy have been added to the mix. Furthermore, “Brexit” is part of this debate and partly a product of it, however this paper doesn't have the space required to examine this. The title of this paper relates to Dick Clement and Ian La Frenais sitcom “Whatever happened to the Likely Lads” (WHTTLL) which was first broadcast by the BBC in 1973. It focusses on the relationship between 2 young men in their late 20's Bob and Terry. They come from the same place, have similar backgrounds and have been friends since childhood. But their lives are now at a crossroads. Whilst Bob is attempting to grasp new opportunities, Terry is skeptical and to some degree baffled by the change going on around him. The future of class in an era of social mobility also raised questions about aspiration and identity. These are questions which are now less prominent within discourse on class. The debate around class today is arguably less concerned with the mainstream and has become focussed on extremes looking at either poverty, criminality, dispossession or sometimes the lifestyles of a superrich elite. In summary then this paper will look at the changing ideas, and narratives that have surrounded social class and social mobility over the past half century within the context of the UK, it will do that by reflecting on my own personal biography and the themes raised in “Whatever happened to the Likely Lads” (WHTTLL).